Group Cohesion and Climate in Cognitive Behavioral Therapy for Individuals with a First-Time DUI. Issue 1 (2nd January 2020) - Cruz, Maricela; Osilla, Karen Chan; Paddock, Susan M.
ABSTRACT: Few studies have examined group cohesion and climate in the substance use disorder treatment literature. We examined whether group cohesion and climate are associated with increased self-efficacy outcomes and reduced drinks per week, binge drinking and DUI behaviors, in a sample of individuals with a first-time DUI receiving either cognitive behavioral therapy (CBT) or usual care. Additionally, we examined whether CBT moderates these relationships. Group measures and drinking outcomes were not significantly associated. This study is the first to provide an in-depth analysis on group processes in DUI settings, and as such, provides important insights into how group processes may differ in a mandated DUI context.